PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA POP UP BOOK DIGITAL TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Alya Amrina Rosyada; Puji Rahayu; Nenden Permas Hikmatunisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to examine the influence of the learning model Problem Based Learning media assisted Pop Up Book digital on critical thinking abilities of elementary school students. Model Problem Based Learning can help students learn through real problem solving processes and can increase student involvement in the learning process, temporarily Pop Up Book digital provides an interactive visual experience to facilitate students' critical thinking skills. This research was conducted in class V elementary school in science learning with the type of research used like an experiment and research design Nonequivalent Control Group Design. The samples used were two classes, namely class V a as an experimental class that used a model Problem Based Learning media assisted Pop Up Book digital and V c as the control class that uses the model Cooperative Learning. The results of this research show that students in the experimental class had better results or experienced an increase in posttest scores compared to the control class. The data collection instruments used in this research were description and documentation questions. Test t (independent sample t-test) on the N-Gain score with a significance level of 0,05 shows a significance value of 0,000, meaning H0 submitted was rejected and H1 accepted. On inferential data using a simple linear regression test, the results obtained were the influence of model learning Problem Based Learning media assisted Pop Up Book digital on students' critical thinking skills by 35.5%. Thus, this research can be concluded that learning with models Problem Based Learning media assisted Pop Up Book digital has an influence on the critical thinking abilities of fifth grade students.